Massive and recurrent diverticular hemorrhage, risk factors and treatment. (September 2016) - Gilshtein, Hayim; Kluger, Yoram; Khoury, Areen; Issa, Nidal; Khoury, Wisam
Abstract: Aim: Diverticular hemorrhage may be massive or recurrent, requiring surgical management. The aim of our study is to define risk factors that predict rebleeding or need for urgent operation in patients with diverticular hemorrhage. Methods: Retrospective study was conducted on patients who were admitted for diverticular hemorrhage. Data pertaining to patient and bleeding characteristics, method of diagnosis, blood transfusion and type of operation were collected. Multivariate analysis model compared patients who experienced single bleeding episode with those with recurrent episodes, and patients who underwent surgery with those who did not. Results: One hundred and four patients met the inclusion criteria. Thirty four patients experienced more than one bleeding episode. Ten patients needed surgery for recurrent bleeding. Five patients presented with hemodynamic instability, none of them required surgical treatment. Neither patients' comorbidity nor anticoagulant and antiaggregant treatments were associated with increased risk for recurrent hemorrhage. Diabetes mellitus was correlated with decreased risk for recurrent hemorrhage, OR = 0.21, (CI 95% (0.06–0.73)); p = 0.014. Independent risk factor for massive recurrent diverticular hemorrhage requiring surgery was right sided diverticulosis, OR = 4.6(CI 95% (2.1–19)); p = 0.006. Conclusions: Right colon diverticulosis rather than patient characteristics and medical treatment should prompt for aggressive management with lower threshold for surgical intervention. Highlights: Diverticulosis site is a risk factor for recurrent diverticular hemorrhage. Right colon diverticular hemorrhage prompt early surgical treatment. Anti coagulant treatment does not increase risk of recurrent bleeding.